2005
DOI: 10.4049/jimmunol.175.3.1523
|View full text |Cite
|
Sign up to set email alerts
|

Specific Role of Phosphodiesterase 4B in Lipopolysaccharide-Induced Signaling in Mouse Macrophages

Abstract: Cyclic nucleotide signaling functions as a negative modulator of inflammatory cell responses, and type 4 phosphodiesterases (PDE4) are important regulators of this pathway. In this study, we provide evidence that only one of the three PDE4 genes expressed in mouse peritoneal macrophages is involved in the control of TLR signaling. In these cells, LPS stimulation of TLR caused a major up-regulation of PDE4B but not the paralogs PDE4A or PDE4D. Only ablation of PDE4B impacted LPS signaling and TNF-α production. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
201
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(221 citation statements)
references
References 40 publications
11
201
1
Order By: Relevance
“…The work presented here shows that the PDE4B subfamily and particularly the PDE4B2 (Jin et al, 2005a;Jin and Conti 2002). In our group we have previously reported a selective increase in PDE4B2 mRNA levels in LPS-treated rats (Reyes-Irisarri et al, 2008) and in brain circumventricular organs of LPS-treated mice (Johansson et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The work presented here shows that the PDE4B subfamily and particularly the PDE4B2 (Jin et al, 2005a;Jin and Conti 2002). In our group we have previously reported a selective increase in PDE4B2 mRNA levels in LPS-treated rats (Reyes-Irisarri et al, 2008) and in brain circumventricular organs of LPS-treated mice (Johansson et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…In the EAE model, amelioration of the clinical signs and delayed onset is observed after PDE4 inhibition with rolipram (Folcik et al, 1999;Moore et al, 2006;Sommer et al, 1995). The PDE4B gene has been related to the inflammatory response in mouse monocytes and macrophages (Jin et al, 2005a) and previous publications by our group have shown that the PDE4B mRNA splice variant PDE4B2 is upregulated in cellular infiltrates of EAE rat brains (Reyes-Irisarri et al, 2007). Furthermore, during innate inflammation the expression of both PDE4B2 and PDE4B3 mRNAs are altered (Johansson et al, 2011;2012b), suggesting a possible role of these enzymes in regulating the cytokine environment during neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…While studies have shown that PDE4D plays an important role in the mediation of antidepressant-like effect (Zhang et al, 2002) and may be involved in memory , the role of PDE4B has not been investigated due to the lack of highly selective inhibitors of individual PDE4 subtypes and the complexity of the PDE4 family in terms of its numerous variants and compartmentation (Conti et al, 2003;Houslay et al, 2005;Terrin et al, 2006). Using mice deficient in PDE4B, it has been demonstrated that this subtype plays a critical role in lipopolysaccharide-induced signaling and inflammatory responses (Ariga et al, 2004;Jin et al, 2005a). Most recently, it has been shown that PDE4B is required for the antipsychotic effect of rolipram (Siuciak et al, 2007), which is consistent with the association of this subtype with schizophrenia (Millar et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Speciically, A33 inhibits all PDE4B isoforms and is 49-fold more selective toward PDE4B compared with PDE4D and does not appreciably inhibit other PDEs [120,121]. Interestingly, TNF-α levels at 6-hour postsurgery of traumatic brain injury (TBI) were signiicantly reduced by A33, suggesting that an inflammatory pathway mediated by PDE4B is inhibited with A33 [122]; [115] (Jin and Conti; Jin et al). However, further studies to determine the antineuroinflammatory mechanisms of A33 may yield insights into the processes involved in the improvements of psychiatric disorders with A33 treatment.…”
Section: Mechanisms Of Neuroinflammationmentioning
confidence: 99%